Adaptation of motor tests for the assessment of math skills in a classroom context - Flores, Pedro Miguel Teixeira (2023)
Mathematics has been documented as a subject in which many school-age children have shown many difficulties and poor maths skills are associated with negative outcomes throughout life, such as lower academic qualifications, decreased professional success and socio-economic results. These maths skills emerge continuously throughout childhood and those that children acquire in preschool are decisive for future learning. In this sense, the earlier mathematical difficulties are diagnosed, the greater the possibility of effective intervention. Thus, as well as offering great opportunities for the holistic development of children, preschool education is a fundamental period for diagnosing possible learning difficulties, particularly mathematical ones. Since there is evidence of a relationship between motor and cognitive development, and that certain cognitive and motor areas of the brain are activated simultaneously when applying maths skills, the diagnosis of these skills can be made from the observation of motor skills. Therefore, in the first phase of this research, the aim of a systematic review was to identify the specific components of motor skills that were most positively associated with mathematical performance in preschool children and to identify the respective instruments used in this association. The main results showed that maths skills were mainly positively influenced by fine motor skills, namely fine motor coordination and visuomotor integration, and the main characteristics of the instruments used showed that tasks involving copying figures or drawings were the most used to assess visuomotor integration and tasks involving handling objects, with pincer movements, were the most commonly used to assess fine motor coordination. Although studies have shown the importance of instruments to assess these skills, their characteristics do not fit the reality of kindergartens, they are usually time-consuming and expensive, and they are generally only administered by specialists. Therefore, a second study was carried out, constituting the main objective of this research, in order to identify, select, adapt and validate motor tests to assess fine motor skills associated with mathematics and allow the kindergarten teacher to apply them simultaneously to the class, with few material resources, in a short period of time and without the need for much training to apply, score and classify. The test identified, selected and adapted to assess fine motor coordination was the "Threading Beads" test from the Movement Assessment Battery for Children and to assess visuomotor integration was the Visual-Motor Integration test. The results suggested that the adapted tests had an excellent degree of reliability (> 0.9) and could therefore be used to apply simultaneously to the class group. However, due to the robust results, the Visual-Motor Integration Adapted test seems to be the most suitable for use by kindergarten teachers. Some literature suggests that gross motor skills are also positively associated with maths performance. In this sense, since early childhood is a sensitive period for the development of motor skills (gross and fine), and low levels of physical activity during this period can compromise their development and contribute to weight gain and obesity, the aim of the third study was to analyse the relationships between maths skills, motor skills, levels of physical activity and obesity. The study concluded that maths skills were only directly and significantly influenced by visuomotor integration skills. However, visuomotor integration was positively and significantly associated with gross motor skills. Therefore, these motor skills could contribute to directly improving visuomotor integration and thus indirectly improving maths skills. This study suggested the implementation of structured physical activity programmes, involving fine and gross motor activities, to develop visuomotor integration skills and thus the possibility of contributing to mathematical performance. Finally, the last study identified the components of visuomotor integration skills that have the greatest influence on these skills and concluded that they would be spatial skills, because as well as being the first skills to influence numerical knowledge and the recognition of geometric shapes, they are also those skills that form part of most of the programs and activities to be worked on with preschool children to develop mathematical concepts. Summarising, this research has made it possible to identify and adapt motor tests to assess fine motor coordination and visuomotor integration that can easily be used by kindergarten teachers to diagnose children with possible mathematical difficulties and to propose a set of activities to develop spatial skills using gross motor skills in the classroom, playground or at home.